The effects of aging on rho-kinase and insulin signaling in skeletal muscle and white adipose tissue of rats - Muñoz, Vitor Rosetto (2020)
The insulin receptor substrate 1 regulates insulin-mediated glucose uptake and is a target of Rho-kinase (Rock); however, the relationship between age-related insulin resistance and Rock signaling specifically in skeletal muscle and adipose tissue is unknown. We evaluated the content and activity of Rock in C2C12 myotubes, and in skeletal muscle and white adipose tissue (WAT) from two rodent models that differ in their patterns of body fat accumulation during aging (Wistar and Fischer 344 rats). Body fat gain in the Wistar rats was greater than in Fischer rats and only Wistar rats had impairment of whole-body insulin sensitivity. Rock activity and insulin signaling were impaired in skeletal muscle in both rat models, but only middle-aged Wistar rats had higher Rock activity in WAT. These data are consistent with a positive role of Rock in regulating insulin signaling in both skeletal muscle and its negative role in the adipose tissue, suggesting that Rock activity in adipose tissue is important in age-related insulin resistance.